2019
DOI: 10.37358/rc.19.7.7373
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Experimental Results on the Recovery of Potato Processing Residuals by Anaerobic Digestion

Abstract: Anaerobic digestion of organic matter with high moisture content has proven to be a suitable method for disposal of wet organic residuals with several advantages compared to other treatment technologies. This paper aimed at evaluating the theoretical and experimental biomethane potential of food processing residuals that are responsible for negative environmental impact, with exemplification for the potato processing waste. The biomethane potential is a useful parameter to assess the economic efficiency of ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Furthermore, in experimental trials there is a wide variety of substances that can inhibit anaerobic processes (Chen et al, 2008). In short, the conversion of organic substances into methane, in the experimental tests, is lower than in the theoretical estimates since the ideal conditions cannot be met (Dima et al, 2019). The tests of this research showed that the data for obtaining biodegradability are adequate, since the results of biodegradability and experimental performance showed a concordance of more than 95% in their coefficient of determination (R 2 ) (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in experimental trials there is a wide variety of substances that can inhibit anaerobic processes (Chen et al, 2008). In short, the conversion of organic substances into methane, in the experimental tests, is lower than in the theoretical estimates since the ideal conditions cannot be met (Dima et al, 2019). The tests of this research showed that the data for obtaining biodegradability are adequate, since the results of biodegradability and experimental performance showed a concordance of more than 95% in their coefficient of determination (R 2 ) (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…It contains phenolic compounds and pesticide residues, used as organic fertilizer after special processing. When the water content of FPW is high, the anaerobic fermentation method is suitable . The organic content in those wastes is first hydrolyzed by the presence of anaerobic microorganisms and produces various short-chain organic acids and other organic products.…”
Section: Traditional Treatment Of Food Processing Wastementioning
confidence: 99%
“…When the water content of FPW is high, the anaerobic fermentation method is suitable. 59 The organic content in those wastes is first hydrolyzed by the presence of anaerobic microorganisms and produces various short-chain organic acids and other organic products. These metabolites are then converted into methane and CO 2 under the action of methanogens.…”
Section: ■ Introductionmentioning
confidence: 99%